2016
DOI: 10.1038/srep32657
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 predicts adverse postoperative prognosis of patients with clear cell renal cell carcinoma

Abstract: Dectin-1, a classical pattern-recognition receptor, was now identified as an important regulator in immune homeostasis and cancer immunity through its extensive ligands binding functions and subsequent cytokines production. The aim of this study was to assess the clinical significance of dectin-1 expression in 290 patients with clear cell renal cell carcinoma (ccRCC) through immunohistochemistry on tissue microarrays. We found that dectin-1 was predominantly expressed on ccRCC cells, in accordance with several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Specifically, a consistent upregulation was observed in LG tumors when stage (1) is fixed (fc 3.38, p -value 0.016) and in stage > 1 when the LG lesion is fixed (fc 2.15, p -value 0.019) ( Table 4 and Table S3 ). In accordance with the tissue proteome [ 60 ], urinary CLEC7A levels appeared to correlate with the higher ccRCC stage. Additionally, its presence in the urine of ccRCC patients also appeared to correlate with a lower grade.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Specifically, a consistent upregulation was observed in LG tumors when stage (1) is fixed (fc 3.38, p -value 0.016) and in stage > 1 when the LG lesion is fixed (fc 2.15, p -value 0.019) ( Table 4 and Table S3 ). In accordance with the tissue proteome [ 60 ], urinary CLEC7A levels appeared to correlate with the higher ccRCC stage. Additionally, its presence in the urine of ccRCC patients also appeared to correlate with a lower grade.…”
Section: Discussionmentioning
confidence: 61%
“…While also known as dectin-1, CLEC7A was originally identified as a pattern-recognition receptor expressed on dendritic cells [ 59 ]. In fact, it was demonstrated that its expression on dendritic cells and macrophages enhances the recognition of N-glycans on cancer cells, aiding natural killer cells in depleting tumor cells [ 60 ]. In this regard, Xia et al, using immunohistochemistry, showed that CLEC7A expression was strongly correlated with a higher stage of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, accumulated evidence has suggested that CLEC7A had dual effects on cancer, namely, inhibiting and promoting cancer ( Tone et al, 2019 ). CLEC7A has been widely studied in pancreatic cancer, kidney cancer, and liver cancer, etc., but the true role of this gene remains controversial ( Seifert et al, 2015 ; Xia et al, 2016 ; Daley et al, 2017 ). CLEC7A, which is highly expressed in M2-like tumor-associated macrophages, is linked to galectin 9, thus leading to tolerogenic macrophage programming and adaptive immunosuppression that contribute to tumor exacerbation ( Daley et al, 2017 ; Zhou et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CLEC7A plays a role in innate immune response, and is thus predominantly expressed in the bone marrow, lymphoid tissue, and blood. High CLEC7A expression has been identified as an adverse prognostic factor in renal cell carcinoma [45].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we aimed to evaluate the validity of the microarray data analyses. Based on strong association with ex vivo towards multiple drugs resistance in the discovery cohort, we selected CLEC7A [45], HIF1A [46,47], and RUNX1 [48] for technical validation in the discovery cohort. Moreover, considering their known role as predictor of survival in AML, and the observed association with ex vivo response in the discovery cohort, we additionally evaluated STAT3 [44] and BRE [49] using qPCR for technical validation in 58 of the 73 patients from the discovery cohort.…”
Section: Technical and Independent Validation Of The Association Between Expression Levels Of Selected Genes And Ex Vivo Drug Responsementioning
confidence: 99%